Implementasi Model Manajemen Berbasis Sekolah (MBS) di SMA Negeri 2 Unggulan Sangatta Utara - Ali, Muhammad (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
School Based Management (SBM) is an effort to develop the education which roots from society, and also become inspired by the society, managed by the society and for society’s needs. School Based Management (SBM) gives school’s authority to the develop the polential. Institution it self dynamically and participatingly. Based on the result of study, there are three factors that make the education quality runs effectively anol it also improves evenly. The third factors are the education policy which concerns about education process, the implementation of education becomes regulative, innovative, and independent then the role of society through the instution of school committees which is participative oriented. In School Based Management (SBM), school has a greater authority to manage the school itself because philosophically, school understands more how situation and conditional of school and also the expectation will be achieved. The purpose of School Based Management (SBM) program are the improvement of education quality includes school management, active learning, creative, effective, and fun (PAIKEM) and the participation of society. The purpose of this study are describing the implementation of School Based Management (SBM), the head master’s performance, teacher, and also the participation of society at SMAN 2 Sangatta Utara including the supporting inhibiting factors. This study used descriptive qualitative methodology the technique of collecting data through interview, Observation, and documentation. The reverence sources are taken from principal, teacher, and society by using the instrument. The result show that firstly, school enables to use internal and external potential to interfere at every strategic activities of school. The next, the implementation of School Based Management (SBM) viewed by the principal’s performance with various duties and functions such as manager, administrator, supervisor, innovator, and motivator runs well. The third, the teachers also show good performance in doing their duties for instances preparation of teaching program, the presentation of the subject matter, evaluation, and the result of student learning analysis and remedial. The last, participation of society good cooperation with the school management. Thus, indicates that the performance of principal and teacher comprehensively the partipation of society through school committees runs in synergy, coordinative, and dynamic in the context of implementation school based management model at SMAN 2 Sangatta Utara.